Your decisions are what you eat: Metabolic state can have a serious impact on risk‐taking and decision‐making in humans and animals. (17th May 2013) - Hunter, Philip
Abstract : Does being hungry affect your judgment? Is a good meal a precursor to a good mood? New research is discovering how metabolic state and the nutritional quality of food influence risk‐taking and decision‐making behaviours in animals and humans.